2008
DOI: 10.1152/ajpregu.90625.2008
|View full text |Cite
|
Sign up to set email alerts
|

The role of inhibitory heterotrimeric G proteins in the control of in vivo heart rate dynamics

Abstract: Zuberi Z, Birnbaumer L, Tinker A. The role of inhibitory heterotrimeric G proteins in the control of in vivo heart rate dynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 48 publications
3
34
0
Order By: Relevance
“…However, emerging data from the analysis of knock-out mice indicates that is some instances there may be little functional redundancy in vivo. For example, Gnai2 −/− mice have a selective defect of parasympathetic modulation of heart rate not seen in Gnai1/Gnai3 double knock-out mice 36. Furthermore, a recent reconstitution study in Sf9 cells that showed CXCL12 induced GTPase activity in cell membrane preparations containing either Gα i1 or Gα i2 exceeded that noted with membranes containing Gα i3 and greatly exceeded those expressing Gα o suggesting that CXCR4 preferentially couples to Gα i1 and Gα i2 37.…”
Section: Discussionmentioning
confidence: 99%
“…However, emerging data from the analysis of knock-out mice indicates that is some instances there may be little functional redundancy in vivo. For example, Gnai2 −/− mice have a selective defect of parasympathetic modulation of heart rate not seen in Gnai1/Gnai3 double knock-out mice 36. Furthermore, a recent reconstitution study in Sf9 cells that showed CXCL12 induced GTPase activity in cell membrane preparations containing either Gα i1 or Gα i2 exceeded that noted with membranes containing Gα i3 and greatly exceeded those expressing Gα o suggesting that CXCR4 preferentially couples to Gα i1 and Gα i2 37.…”
Section: Discussionmentioning
confidence: 99%
“…Details of telemetry system (TEA-F20, DSI, St Pauls) implantation have previously been described 20 . Recording leads were tunnelled subcutaneously in a conventional “Lead II” ECG configuration to continuously record surface ECG after a 2 week period of surgical recovery.…”
Section: Methodsmentioning
confidence: 99%
“…These studies suggested that GIRK1/4 activation by the m2R receptor is mediated by Gα i2 or Gα i3 (Fu et al, 2006;Sowell et al, 1997) but not via Gα o , despite the abundance of the latter (Luetje, Tietje, Christian, & Nathanson, 1988) and despite its specific participation in m2R coupling to voltage-dependent Ca 2+ channels in the heart (Valenzuela et al, 1997;Ye, Sowell, Vassilev, Milstone, & Mortensen, 1999). The selective role of Gα i2 but not Gα i1 or Gα o in the muscarinic activation of cardiac GIRK has been confirmed in Gα knockout mice (Zuberi, Birnbaumer, & Tinker, 2008). The exquisite selectivity observed in the heart cannot be easily reconstituted in heterologous systems, where all Gα i/o species can donate Gβγ to activate GIRKs.…”
Section: Specificity Of Gpcr-girk Signaling: Relative Roles Of Gα Andmentioning
confidence: 98%